HUBUNGAN PENGETAHUAN SIKAP DAN PERILAKU IBU TENTANG STIMULASI DENGAN PERKEMBANGAN MOTORIK KASAR ANAK USIA 3¬-5 TAHUN DI DESA PUAU TELUK NIBUNG KECAMATAN PULAU BANYAK KABUPATEN ACEH SINGKIL TAHUN 2020 - llinda purwanti (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2023)
Gross motor development is related aspects by movement and posture and usually requires power, because performed by a large body muscle. Good rough motor development not only supported through fulfillment of nutrition, however also supported by stimulation that given. The role of a mother in child care, also in giving stimulation on child very big. The purpose of this study was to identify the relationship of mother's knowledge about developmental stimulation with gross motor development of children aged 3-5 years in the Village Pulau Teluk Nibung Districk Pulau Banyak Regacy of Aceh Singkil. This research is Deskriptif Korelasi with approach Cross Sectional. The total population of research as many as 110 people. Sampling technique is done by total sampling of the population so that the number of sample counted 110 people. Power analysis used Uji Chi Square. The results show there is a close relationship between mother's knowledge about stimulation with gross motor development of children aged 3-5 years in the Village Pulau Teluk Nibung Districk Pulau Banyak Regacy of Aceh Singkil, where knowledge P value = (0,004), attitude P value = (0,003), behavior P value = (0,002). Conclusion there is a relationship of mother knowledge about stimulation with groos motor development of children aged 3-5 years in the Village Pulau Teluk Nibung Districk Pulau Banyak Regacy of Aceh Singkil. It is suggested to mothers in order to dig deeper information from sources that are accurate about the importance and how to stimulate gross motor development of children.